Digital Entrepreneurship and Financial Performance: The Mediating Role of Innovation Capability in SMEs India - Sandhi Nasrudin Wibowo; Swetha Rajput (Journal of Business Innovation and Accounting Research, 2025)
The rapid advancement of digital technologies has fundamentally transformed entrepreneurial landscapes, particularly within small and medium enterprises (SMEs) in emerging economies. This study investigates the relationship between digital entrepreneurship and financial performance, with specific emphasis on the mediating role of innovation capability among Indian SMEs. Drawing upon resource-based view and dynamic capabilities theory, this research employs a quantitative methodology utilizing structural equation modeling with partial least squares (PLS-SEM) to analyze data collected from 385 SME owner-managers across major industrial clusters in India. The findings reveal that digital entrepreneurship significantly enhances financial performance, with innovation capability serving as a partial mediator in this relationship. Specifically, digital technology adoption demonstrates a positive and significant effect on both innovation capability (β = 0.412, p < 0.001) and financial performance (β = 0.287, p < 0.01). Furthermore, innovation capability exhibits a substantial mediating effect, accounting for approximately 38.7% of the total effect between digital entrepreneurship and financial performance. The results underscore the critical importance of developing innovation capabilities as a strategic mechanism through which digital entrepreneurship initiatives translate into superior financial outcomes. These findings contribute to the theoretical understanding of digital transformation in emerging market contexts and provide practical implications for SME managers and policymakers seeking to leverage digital technologies for enhanced business performance.